Competency Level of Grade Six Teachers Based on Performance Evaluation Scorecard in Relation to Division Unified Testing Program (DUTP) Result - Espetacion, Hyacinth Joy (IJRDO- Journal of Educational Research, 2020)
The study identified the competency level of grade six teachers based on performance evaluation scored and its relation to pupil’s Division Unified Testing Program (DUTP) result. The study was descriptive-correlational in nature. The statistical tools used were the following: percentage, weighted mean μ, mean, spearman rank correlation coefficient,and Point-Biserial Correlation.The study found out that majority of the grade six teachers was female who are either young or old. Most of them have MA units and have been teaching for at least a year to ten years. The study revealed that majority of the grade six teachers were in the outstanding level based on their performance evaluation scorecard. The study also indicated that majority of the grade six pupils performed at the “beginning” level based on their DUTP result.The study also indicated that there is a low/slight relationship between the grade six teachers’ competency level based on the performance evaluation scored and their pupil’s Division Unified Testing Program (DUTP) result. However, Teachers’ profile has a negligible relationship to their levels of competence.